Bothropoides insularis venom cytotoxicity in renal tubular epithelia cells - Mello, Clarissa P.; Morais, Isabel C. O.; Menezes, Ramon R. P. P. B.; Pereira, Gustavo J. S.; Torres, Alba F. C.; Lima, Danya B.; Pereira, Ticiana P.; Toyama, Marcos H. [UNESP]; Monteiro, Helena S. A.; Smaili, Soraya S.; Martins, Alice M. C. (Elsevier B.V., 2014)
Bothropoides insularis (jararaca-ilhoa) is a native endemic snake limited to the specific region of Queimada Island, on Sao Paulo coast. Several local and systemic effects have been described due to envenomation caused by it, such as edema, tissue necrosis, hemorrhage and acute renal failure. Our previous studies have shown that Bothropoides insularis venom (BinsV) demonstrated important functional and morphologic alterations in rat isolated kidney, especially decrease in tubular electrolyte transport, osmotic clearance and tubular necrosis. In order to elucidate the direct nephrotoxicity mechanism, the aim of the present study was to investigate BinsV cytotoxicity effect on renal epithelial cells. The treatment with BinsV over MDCK culture decreased cell viability in all concentrations tested with IC50 of 9 mu g/mL. BinsV was able to induce membrane rupture and cell death with phosphatidilserine externalization. Furthermore, BinsV induced ROS overproduction and mitochondrial membrane potential collapse, as well as Bax translocation and caspases 3 and 7 expression. Therefore, these events might be responsible by BinsV-induced cell death caused by mitochondrial dysfunction and ROS overproduction in the direct cytotoxicity process. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bothropoides insularis venom; Nephrotoxicity; Cell death